European Stroke Organisation (ESO) guideline on visual impairment in stroke - Rowe, Fiona J; Hepworth, Lauren R; Begoña Coco-Martin, María; Gillebert, Celine R; Leal-Vega, Luis; Palmowski-Wolfe, Anja; Papageorgiou, Eleni; Ryan, Stephen James; Skorkovska, Karolina; Aamodt, Anne Hege (European stroke journal, 2025)
Visual impairment due to stroke is common. However, controversy exists on how best to screen for visual impairment, the timing at which to screen, and on the optimal management of the varying types of visual impairment. This European Stroke Organisation (ESO) guideline provides evidence-based recommendations to assist clinicians in decision-making on screening methods, timing of screening and assessment and management options in adult stroke survivors. The target audience for this guideline is health care providers involved in stroke care from prehospital screening, in stroke units and rehabilitation centres, ophthalmological departments and community stroke care, and for stroke survivors and care givers. The guideline was developed according to the ESO standard operating procedure and the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) methodology. The working group identified relevant clinical questions, performed systematic reviews and, where possible, meta-analyses of the literature, assessed the quality of the available evidence and made specific recommendations. Expert consensus statements were provided where insufficient evidence was available to provide recommendations based on the GRADE approach. We found evidence of acceptability and feasibility of early visual screening within 1 week of stroke onset. We describe the accuracy of various vision screening tools at pre-hospital and hyper/acute stages as well as specialist vision assessment. We suggest vision screening in all patients with stroke to improve detection of their visual problems We describe a range of treatment options for visual impairment post-stroke across the typical categories of impaired central vision, ocular stroke (central retinal artery occlusion), eye movements, visual fields, visual neglect and visual perception. This guideline highlights specific areas where robust evidence is lacking and where further definitive randomised controlled trials and diagnostic accuracy studies are required.
Keywords: ocular stroke; systematic review; treatment; screening; visual perception; visual impairment; vision; stroke; Guideline; visual neglect; visual fields; eye movements